Microsite and grazing intensity drive infiltration in a semiarid woodland. Issue 4 (25th January 2017) - Vandandorj, Sumiya; Eldridge, David J.; Travers, Samantha K.; Val, James; Oliver, Ian
Abstract: Human activities such as vegetation removal and overgrazing that result in changes in land cover have substantial impacts on ecosystem processes, including the infiltration of water. Different land cover types (microsites) vary in their capacity to conduct water, but the extent to which infiltration is affected by different herbivores or microsites is largely unknown. We examined the effects of grazing and microsite on infiltration in two extensive woodland communities in semiarid eastern Australia that vary in current condition. Poor condition sites had lower steady‐state infiltration under ponding than either average or good condition sites, and this effect was consistent across the two communities. Ponded infiltration and sorptivity beneath grasses, shrubs or trees were about twice that on bare soil, and this corresponded to greater indices of macroporosity. Structural equation modelling showed that shrubs, trees, and grasses had strong positive effects on sorptivity and steady‐state infiltration under ponding, whereas grazing had generally negative effects. The suppressive effects of grazing on soil hydrological processes were mainly due to cattle grazing. The positive effects of grasses, shrubs, and trees on hydrology were twice as strong as the negative effects of grazing. Our results also suggest that prolonged overgrazing that leads to reductions in grass cover is likely to have a synergistic reduction in hydrological function in these woodlands by reducing the cover of highly conductive patches and by reducing the extent of macropores.